Characteristic Analysis of High-Speed PMSG According to Winding Distribution - Shin, Kyung-Hun; Yoon, Ick-Jae; Nah, Junghyo; Choi, Jang-Young (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this study, we investigate the distribution of windings with optimum performance from the performance analysis according to the winding distribution of a high-speed permanent magnet synchronous generator (PMSG).Methods/Statistical analysis: Electromagnetic parameters of the high-speed PMSG are derived using the finite element analysis. The relationship between the winding coefficient and the electromagnetic parameter is defined, and the change in the parameters, according to the winding distribution, is confirmed. The generating characteristics analysis is performed using the equivalent circuit method (ECM), and the efficiency characteristics are analyzed from the ECM and the loss analysis.Findings: This paper presents the influence of winding distribution on the electromagnetic performance of high-speed PMSGs. The factors affecting the performance of the PMSG are back electromotive force (EMF), inductance, and resistance. As regards low-speed PMSGs, back EMF and resistance generally have a large effect on performance. However, as regards a high-speed PMSG, the reactance increases as the operating frequency increases. Therefore, inductance, as well as back EMF and resistance, are the main factors affecting performance. We propose a method to select the optimal winding distribution based on the investigation of the influence of the winding distribution on the electromagnetic performance using the ECM considering loss characteristics.Improvements/Applications: Based on the analysis results, it is possible to use winding distribution as a design point in both the initial and optimum designs of the high-speed PMSG.Â Â